Analisis Soal Pilihan Ganda Pada UTS PKn Semester Gasal Kelas IV SD Tahun Ajaran 2017/2018 di Kecamatan Banjarnegara - Sari Yustiana; Dynar Rizqi Mara Romadhoni (Jurnal Inovasi Pendidikan Dasar, 2017)
This study aims to analyze the question of multiple choice of “UTS semester gasal” of Civic education, class IV elementary school year 2017/2018 in District Banjarnegara, a number of 35 questions. The problem was analyzed based on validity, reliability, difficulty level, distinguishing power, and distractor matter. The calculation was done by using Itemen version 3.0 program. Selection of the Itemen program because the program can analyze multiple choice questions. Based on the results of the analysis, the validity of the questions there were 1 invalid questions (2.86%), and 34 valid questions (97.14%). The result of reliability coefficient was 0.839, which means reliability. The result of difficulty level there were 3 questions in the category is too difficult (8,5%), 24 matter enough category / medium (68,5%), and 8 matter too easy category (23%). There was no questions in the category of very bad, there were 1 questions in bad category (3%), 4 questions enough category (11%), 30 questions in good category (86%), and no question in very good category. Furthermore, in distractor, there were 20 questions with distractor that works well (57%), the remaining number is 15 questions with distractor not working (43%).